2018
DOI: 10.3389/fpls.2018.01279
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Gibberellin Acid Mutual Induction to Regulate Tobacco Seed Germination

Abstract: Seed germination is a complex process controlled by various mechanisms. To examine the potential contribution of reactive oxygen species (ROS) and gibberellin acid (GA) in regulating seed germination, diphenylene iodonium chloride (DPI) and uniconazole (Uni), as hydrogen peroxide (H2O2) and GA synthesis inhibitor, respectively, were exogenously applied on tobacco seeds using the seed priming method. Seed priming with DPI or Uni decreased germination percentage as compared with priming with H2O, especially the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 71 publications
(88 reference statements)
2
21
0
Order By: Relevance
“…In one way, increase in ROS content, which is beneficial for germination, is associated with alteration of synthesis and signalling of ABA, the hormone which represses germination. It has been demonstrated that H 2 O 2 accumulation in germinating seeds was associated with ABA degradation probably trough an activation of ABA-8-hydroxylase, an ABA catalytic enzyme [26,30,33,53,79] even though a direct oxidation of ABA cannot be excluded [51,95,96]. ABA being regulating germination by its antagonistic interaction with GA it is worth noting that ROS have been reported to stimulate GA biosynthesis through a transcriptional effect [28,32,33,53,79].…”
Section: Ros Crosstalk With Germination Signalling Pathwaysmentioning
confidence: 99%
“…In one way, increase in ROS content, which is beneficial for germination, is associated with alteration of synthesis and signalling of ABA, the hormone which represses germination. It has been demonstrated that H 2 O 2 accumulation in germinating seeds was associated with ABA degradation probably trough an activation of ABA-8-hydroxylase, an ABA catalytic enzyme [26,30,33,53,79] even though a direct oxidation of ABA cannot be excluded [51,95,96]. ABA being regulating germination by its antagonistic interaction with GA it is worth noting that ROS have been reported to stimulate GA biosynthesis through a transcriptional effect [28,32,33,53,79].…”
Section: Ros Crosstalk With Germination Signalling Pathwaysmentioning
confidence: 99%
“…On the other hand, ABA was shown to prevent the accumulation of ROS within the embryonic axis of the seeds [33]. Currently, the interactions between ROS and ABA/GA are still under debate [36]. The role of ROS in seed germination is dual and is defined as the oxidative window of germination [37].…”
Section: Seed Germinationmentioning
confidence: 99%
“…Seed dormancy and germination are complex processes regulated mainly by the plant hormones gibberellins (GAs) and abscisic acid (ABA). Environmental and endogenous factors might control the abundance of signaling molecules which determine the ABA/GAs ratio, thus elevated ABA concentration within seeds triggers seed dormancy while high GAs level induces germination (Bailly et al, 2008;Graeber et al, 2012;Li et al, 2018). There are different definitions and classifications of seed dormancy; a delay or fail to germinate under favorable conditions is a generally accepted definition (Arc et al, 2013).…”
Section: Introductionmentioning
confidence: 99%